Diseases of Bitter Melon in South Florida - Shouan Zhang; Mary Lamberts; Gene McAvoy (EDIS)
Bitter melon, a tropical and subtropical cucurbit, is widely grown in Asia, Africa, and the Caribbean for its edible fruit. Rich in vitamins A and C, iron, and phosphorus, it contains a compound (charantin) that has been used to lower blood sugar levels to treat diabetes. Two major types of bitter melon, Chinese and Indian, are grown in South Florida year-round. This publication describes common diseases and provides recommendations for their control. This 3-page fact sheet was written by Shouan Zhang, Mary Lamberts, and Gene McAvoy, and published by the UF Department of Plant Pathology, October 2012.